2013
DOI: 10.4028/www.scientific.net/amr.832.843
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Spectra of ZnO Thin Film Composed Nanoparticles on Silicon and Porous Silicon

Abstract: ZnO thin film was successfully deposited on different substrate by sol-gel spin coating. Zinc acetate dihydrates, diethanolamine and isopropyl were used as starting material, stabilizer and solvent respectively. Two different substrate used in this work are p-type silicon wafer and porous silicon. Porous silicon was prepared by electrochemical etching. In order to study the surface morphology, field emission scanning electron microscopy (FESEM) was employed. It is found that, ZnO thin film was composed by ZnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Compared to NR, PL intensities of NF appear to be much higher, signifying a different defect mechanism within the structure, which requires a more detailed investigation. The appearance of the NBE peak at ∼430 nm, which is slightly red-shifted compared to other NBEs reported in the literature, can be attributed to a smaller bandgap of NF structures . Additionally, the variation in the concentration of native defects can also be responsible for the shift in the NBE peak of ZnO NF.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Compared to NR, PL intensities of NF appear to be much higher, signifying a different defect mechanism within the structure, which requires a more detailed investigation. The appearance of the NBE peak at ∼430 nm, which is slightly red-shifted compared to other NBEs reported in the literature, can be attributed to a smaller bandgap of NF structures . Additionally, the variation in the concentration of native defects can also be responsible for the shift in the NBE peak of ZnO NF.…”
Section: Resultsmentioning
confidence: 51%
“…The appearance of the NBE peak at ∼430 nm, which is slightly red-shifted compared to other NBEs reported in the literature, can be attributed to a smaller bandgap of NF structures. 53 Additionally, the variation in the concentration of native defects can also be responsible for the shift in the NBE peak of ZnO NF. Several studies reported on defect contents in ZnO have indicated that the number of defects on the surface is higher than those existing within the bulk volume.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A mixture of HF 48% and absolute ethanol was used as electrolyte. The circuit was supplied with voltage of 100 V, and current densities of 20 mA/cm 2 [10]. The porous silicon was seeded by ZnO thin film using spin coated [11,12].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, good chemical and thermal stability, non-toxic material and high transparency in room temperature are additional advantages in devices fabrication [2]. There are various structures of ZnO have been produced such as nanoparticles, nanorods, nanowires, nano-flower and honey-comb [3][4][5][6]. The structure are highly depends on the methods applied such as hydrothermal, RF sputtering, sol-gel synthesis and pulsed laser ablation [7].…”
Section: Introductionmentioning
confidence: 99%